DANSAC A/S v SALTS HEALTHCARE LTD. Issue 2 (11th September 2019) - ,
Abstract: H1 Trade marks – Infringement – Parallel imports – Medical devices – Ostomy bags – Strike out application – Sale in original unopened boxes – Some boxes re-labelled – Whether the BMS conditions applied – Whether any risk to guarantee of origin – "Legitimate reasons" for opposing further dealings – Whether breach of Medical Devices Regulations of itself sufficient – Whether likelihood of damage or serious damage necessary